KLF5 enhances CXCL12 transcription in adipose-derived stem cells to promote endothelial progenitor cells neovascularization and accelerate diabetic wound healing - Yunjia Xie; Xuejun Ni; Xiaofen Wan; Nating Xu; Lu Chen; Chensheng Lin; Xi Zheng; Beichen Cai; Qian Lin; Ruonan Ke; Tao Huang; Xuefeng Hu; et al. (Cellular & Molecular Biology Letters)
Abstract Background Adipose-derived stem cells (ADSCs) have been shown to accelerate diabetic wound healing by promoting neovascularization, though the underlying mechanisms are not fully understood. This study aims to explore whether ADSCs influence endothelial progenitor cells (EPCs) function to enhance diabetic wound healing. Methods Human adipose-derived stem cells (hADSCs) were isolated from patient adipose tissue and cultured under normal and high glucose (HG) conditions. RNA sequencing analyzed gene expression, while immunofluorescence validated findings in patient wound tissues. Mouse adipose-derived stem cells (ADSCs) from C57BL/6 mice were evaluated in vitro for their effects on EPCs under HG using EdU, Transwell, and tube formation assays. A diabetic mouse wound model was used to assess ADSCs therapeutic effects via digital imaging, histology, and immunofluorescence. Kruppel-like factor 5 (KLF5), identified via the JASPAR database, was confirmed by immunohistochemistry and immunofluorescence. KLF5 and C-X-C motif chemokine 12 (CXCL12) expression levels were measured by enzyme-linked immunosorbent assay (ELISA), western blot, and quantitative reverse transcription polymerase chain reaction (RT-qPCR), and their relationship was validated through dual-luciferase assays. Results We constructed a neovascularization-related signature (NRS) comprising 75 genes on the basis of differentially expressed genes (DEGs) linked to neovascularization. GO and KEGG analyses revealed that the NRS is primarily involved in vasculature development and receptor–ligand activity. Seven hub genes (CD34, CXCL12, FGF7, FGF18, FGF1, TEK, KIT) were identified and validated. In a diabetic mouse model, CXCL12 knockdown in ADSCs reduced their ability of promoting wound healing and neovascularization. KLF5 expression was lower in patients with diabetic ulcers and diabetic mice wound tissues compared with normal tissues, while ADSCs treatment significantly increased KLF5 expression in diabetic mice wounds. Dual-luciferase reporter assays confirmed KLF5 as an upstream transcription factor of CXCL12. Additionally, knocking down KLF5 in ADSCs impaired their therapeutic effects on diabetic wound healing. In vitro, the addition of exogenous CXCL12 recombinant protein restored EPCs proliferation, migration, and vasculogenic capacity in a high glucose environment after KLF5 silencing in ADSCs. Conclusions Our findings underscore the pivotal role of KLF5 in enhancing CXCL12 transcription within ADSCs, thereby facilitating EPC-mediated neovascularization and improving diabetic wound healing. Additionally, KLF5 emerges as a promising therapeutic target for accelerating tissue repair in diabetic wounds. Graphical Abstract